Chemical vapor deposition of clean and pure MoS2 crystals by the inhibition of MoO3−x intermediates. Issue 1 (21st November 2020) - Guan, Ran; Duan, Junxi; Yuan, Aiheng; Wang, Zhuofan; Yang, Shuai; Han, Luoqiao; Zhang, Bo; Li, Dejun; Luo, Birong
Abstract : A sublimated sulfur vapor versus evaporated MoO3 vapor with transition from low to high sulfur supersaturation would cause different CVD products transformed from MoS2 –MoO3− x composites to clean and pure MoS2 crystals accordingly. Abstract : Molybdenum disulfide (MoS2 ) synthesized via chemical vapor deposition (CVD) is commonly accompanied by some intermediate products in the form of MoO3− x, resulting in MoS2 –MoO3− x hybrids with diverse structures. In this study, we show that through the rational design of heating evaporation rate of the precursors of sulfur and MoO3 separately in a CVD system with double temperature zones, the intermediate product of MoO3− x involved in the CVD growth of MOS2 (generally in the form of quadrilateral MoO2 /MoS2 composites and/or stacks of quadrilateral MoO2 /triangular MoS2 ) can be inhibited largely. On this basis, the appropriate sulfur sublimation versus the evaporated MoO3 powder is revealed to be the key factor for the inhibition of intermediates, obtaining high-quality MoS2 crystals with as high as >90% cleanness/purity. This study will assist our understanding of the fundamental CVD growth mechanisms of transition metal dichalcogenides (TMDCs) and provides a facile direction for the controlled synthesis of high-quality MoS2 and other TMDCs with or without intermediate hybrids for applications.